Imaging characteristics of nontuberculous mycobacterial pulmonary nodules - Nishino Kengo (Sciendo, 2021)
Introduction. Nontuberculous mycobacteriosis (NTM) of the lungs can develop nodules. In order to clarify some of the characteristics of lung NTM nodules, we examined volume doubling time (VDT) and maximum standardized uptake value (SUVmax) in positron emission tomography (PET) of pathologically diagnosed NTM nodules.